ACCOUNTING STUDENTS’ ACADEMIC MISCONDUCT AS THE CORRUPTIVE BEHAVIOR: WHAT ACADEMIC FACTORS INFLUENCING? - Suwaldiman Suwaldiman; Irlya Noerofi Tyas (Universitas Agung Podomoro, 2019)
This research was conducted because the consideration of the widespread of students’ corruptive behavior in term of academic misconducts. This research examines the impact of students’ academic performance on their corruptive behavior perception. The data samples are the accounting students of Economics Faculty of Universitas Islam Indonesia. The corruptive behavior is defined as the academic misconducts that are usually done by students. It is measured by their tolerance perception of the academic misconducts. The academic performance is defined and measured as the students’ achievements on the subjects undertaken. These are represented by grade point average (GPA), grade of financial accounting and auditing subjects. A regression analysis is employed to test whether those academic performance have significant impact to the corruptive behavior perception. Based on the analysis, it is found that the GPA and the grade of financial accounting subjects have a positive and significant impact on the corruptive behavior perception. It is suggested that the better performance achieved by students on GPA and these subjects, the better their perception of corruptive behavior. However, this research does not prove that the grades of auditing subjects have a significant impact on the corruptive behavior perceive.